Implementasi Augmented Reality dalam Mata Pelajaran Pekerjaan Dasar Teknik Mesin di SMK Negeri 1 Sumatera Barat - Satria, Lucky; Primawati, Primawati; Purwantono, Purwantono; Prasetya, Febri (Lembaga Yasin AlSys, 2023)
Students' understanding of science is limited because the teacher's lecturing teaching method. This method makes students uninterested in following the learning process. This research is aiming to see what extent the Augmented Reality(AR) applicationcan influence students' learning perceptions. In this research, total sampling method was used with a case study approach. Data was collected through classroom observations, interviews with students, and content analysis of student responses to the use of AR as a learning media. The collected data was analyzed thematically to identify patterns of students' perceptions regarding the benefits, constraints, and responses to using AR. Results from 35 students showed that the use of AR in Mechanical Engineering Basic Work subject received positive responses with 92.5% in scores. Students report that using AR increases interest and engagement in learning, and helps them understand technical concepts better. However, several obstacles such as device limitations and initial training in the use of the technology were also identified. This research emphasizes the importance of integrating AR technology in mechanical engineering education at the vocational school level. These findings provide a vision of the impact of using AR in practical and technical learning, and provide a basis for the development of more better learning strategies. Overall, this study provides valuable insights into students' perceptions of using AR in the context of mechanical engineering education. The implications of these findings can help educators and curriculum developers to design learning experiences that are more engaging and effective in preparing students for future technical challenges.